2006
DOI: 10.1016/j.molcel.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Mechanism for AKAP Binding to RII Isoforms of cAMP-Dependent Protein Kinase

Abstract: A kinase-anchoring proteins (AKAPs) target PKA to specific microdomains by using an amphipathic helix that docks to N-terminal dimerization and docking (D/D) domains of PKA regulatory (R) subunits. To understand specificity, we solved the crystal structure of the helical motif from D-AKAP2, a dual-specific AKAP, bound to the RIIalpha D/D domain. The 1.6 Angstrom structure reveals how this dynamic, hydrophobic docking site is assembled. A stable, hydrophobic docking groove is formed by the helical interface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
236
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(246 citation statements)
references
References 32 publications
10
236
0
Order By: Relevance
“…This is a novel and unique advantage. The crystal structure of the PKA anchoring domain is known (22), and small nonpeptide molecules can be readily developed to target this domain. These small molecules can be further tailored to target ABCA1-expressing cells, which would allow cholesterol removal specifically from foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is a novel and unique advantage. The crystal structure of the PKA anchoring domain is known (22), and small nonpeptide molecules can be readily developed to target this domain. These small molecules can be further tailored to target ABCA1-expressing cells, which would allow cholesterol removal specifically from foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…value of 2.1 Å (Supplementary information, Figure S7B). In the PKA-RIIa/D-AKAP2 complex, the D-AKAP2 peptide forms a helical structure and binds to the hydrophobic cleft on the dimeric interface of PKA RIIa [10]. Notably, secondary structure prediction analysis suggested that, similar to the D-AKAP2 helix, residues 510 to 523 of Ash2L also likely adopt an α-helical structure (data not shown).…”
Section: Dear Editormentioning
confidence: 97%
“…DPY30 DD adopts a canonical four-helix-bundle conformation with extensive hydrophobic surface [9]. The structure of DPY30 DD is similar to that of PKA RIIa, the RIIa isoform of a cAMP-dependent protein kinase [10]. The two structures can be superimposed with an r.m.s.d.…”
Section: Dear Editormentioning
confidence: 99%
“…To date 47 human AKAP genes have been identified that encode proteins which direct PKA to defined intracellular locations (22,23). The majority of these sequester type II PKA subtypes (24)(25)(26), although several dual-function AKAPs can bind either RI or RII (27)(28)(29). Here we report that sphingosine kinase interacting protein (SKIP) anchors the type I PKA holoenzyme exclusively.…”
mentioning
confidence: 95%